Transposition of the Initial Creation of Women in the Qur’an to the Bible (Al-Kitab): Julia Kristeva’s Intertextuality Analysis - Aziz Bashor Pratama (Yinyang: Jurnal Studi Islam Gender dan Anak, 2024)
This paper examines the Qur’ānic transposition of the concept in Bible (Al-Kitab) regarding the creation of women originating from the rib of men. This discussion does not seem to emerge from an explicit narrative in the Qur’anic text but rather from interpretations and hadiths narrated by Bukhari and Muslim. This study addresses two main questions: (1) What is the concept of the initial creation of women in the Qur’an and Al-Kitab? (2) How does the Qur’an transpose this concept to Al-Kitab? Using Julia Kristeva’s intertextuality approach, the research reveals that the transposition involves several elements: namely; the connection of substance or excerpt regarding the purpose of the creation of pairs to complement each other and produce offspring, the contradiction between the text of the Qur’an and Al-Kitab which contains elements of haplology occurs in the abrogation of the Qur’anic text which states that women come from the ribs of men, defamiliarization or changes in meaning conveyed by the Qur’an implicitly about the initial creation of women and demystification which occurs when the Qur’anic text changes the definition of the initial creation of women who are the same as men so that this difference creates Qur’anic opposition to the concept of Al-Kitab or conversion.